Essays in Household Finance - Tobin Hanspal (Copenhagen Business School (CBS), 2017)
This Ph.D. thesis, entitled Essays in Household Finance, analyzes the determinants and implications of investment biases, personal experiences in financial markets, and financing disruptions on households, individual investors, and entrepreneurs and small business owners. The first essay of this thesis, Once Bitten, Twice Shy: The Role of Inertia and Personal Experiences in Risk Taking, with Steffen Andersen and Kasper Meisner Nielsen, studies how personal experiences affect individual financial risk taking. An important concern with pre-existing studies on the effect of personal experiences on risk taking is the potential bias resulting from inertia and inattention, which has been shown to be endemic in household finance. If individuals are inert or inattentive, it is difficult to establish whether changes in risk taking are caused by personal experiences or whether the change in risk taking is due to inertia and movements in market prices. To separate the effect of personal experiences from the confounding effect of inertia, we use an identification strategy that relies on a sample of individuals who inherit a portfolio of risky assets as a result of the death of their parents. The main advantage of this identification strategy is that inheritances from estates that hold risky assets alter the active decision from one of choosing to take risk to one of choosing not to take risk. Our measure of experience derives from investments in banks that defaulted following the financial crisis. We classify experiences into first-hand experiences, resulting from personal losses; second-hand experiences, from the losses of close family members; and third-hand experiences, from living in municipalities where banks defaulted. Our results demonstrate that experiences gained personally, aside from inertia or common shocks, explain substantial heterogeneity in individuals' risk taking.
hdl:10398/9457
Keywords: 650